Keeping an eye on noisy movements: On different approaches to perceptual-motor skill research and training - Dicks, M.; Button, C.; Davids, K.; Chow, J. Y.; van der Kamp, J. (Sports Medicine, 2017)
Contemporary theorizing on the complementary nature of perception and action in expert performance has led to different emphases in the study of movement coordination and gaze behavior. On the one hand, coordination research has examined the role of variability in movement control, evidencing that variability facilitates individualized adaptations during both learning and performance. On the other hand, and at odds with this principle, the majority of gaze behavior studies have tended to average data over participants and trials, proposing the importance of universal `optimal` gaze patterns in a given task, for all performers, irrespective of stage of learning. In this article, we discuss new lines of inquiry with the aim of reconciling these two distinct approaches. We consider the role of inter- and intra-individual variability in gaze behaviors and suggest directions for future research.